Christianity and Education Courses in Guizhou - TAN, Houfeng (Journal of Research for Christianity in China (JRCC), 2025)
After Christianity was introduced to Guizhou, it became inextricably linked to the transformations of modern Guizhou society, with its activities spanning multiple domains. This article systematically examines the educational endeavors undertaken by Christianity in modern Guizhou. While spreading the Christian “Gospel,” the church established various educational institutions in Guizhou, including kindergartens, primary schools, secondary schools, universities, and special schools. The Christian churches established these institutions in Guizhou with the objective of using education as a vehicle to spread the Gospel, thereby attracting more converts and expanding the church's influence. However, these church schools also played an important role in disseminating modern natural and social sciences, introducing Western educational systems and methodologies, and objectively cultivating a large number of talented individuals beneficial to society. They exerted a significant impact on the development of modern education and social progress in Guizhou.